2018
DOI: 10.21512/humaniora.v9i2.4262
|View full text |Cite
|
Sign up to set email alerts
|

Slang Created and Used in 1Cak.com Site: A Sociolinguistics Study

Abstract: This research investigated the slang created based on word formation processes as well as a its functions, and to describe the social factors influencing the existence of slang. The form of this research was qualitative method which resulted in descriptive data. The data were collected by using observations method (screenshot) on the meme or posts which follow certain postings of pictures. Then, it was followed by full observation method for there to be no interference from the researcher on the data collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 9 publications
(5 reference statements)
1
16
0
1
Order By: Relevance
“…Blending process also appeared in the research conducted by Harared (2018) as well as Haspo and Rosa (2018).…”
Section: Blendingmentioning
confidence: 76%
See 3 more Smart Citations
“…Blending process also appeared in the research conducted by Harared (2018) as well as Haspo and Rosa (2018).…”
Section: Blendingmentioning
confidence: 76%
“…This research finds out that clipping is the most dominant process that appears in the lyrics of Drake's songs (52 slang words or 27% of the total data). Similarly, both Haspo & Rosa (2018) and Harared (2018) find out that clipping process is also the most dominant process that appears in 1cak.com site and Eminem song lyrics. This finding implies that slangs that are commonly found and used nowadays are in the form of clipped form of certain words.…”
Section: Clippingmentioning
confidence: 84%
See 2 more Smart Citations
“…In line with it, Harared and Iriyansah (2019) found that the slang word's social function became the reason for slang user convey the slang word. Besides, Harared (2018) explains that slang word's social function is vital since it provokes strong emotion among the groups regarding their closeness and encourages hostility for those who do not share the same slang. In other words, many online communications flow deeper and more expressive because it is frequently done in a group with the same interest.…”
Section: The Social Function Of Slang Wordsmentioning
confidence: 99%